PENANGANAN ANAK HIPERAKTIF MELALUI PERMAINAN PUZZEL DI RA DIPONEGORO KECAMATAN SUKOREJO KOTA BLITAR JAWA TIMUR TAHUN PELAJARAN 2024/2025 - Nunun Lufiana; Taqwatul Uliah; Dewi Yanti (UNISAN JURNAL, 2025)
Hyperactive children often face challenges in managing their energy and attention, which affects their learning process. Puzzle games, as a method to redirect children’s energy into a more structured form, have been implemented at RA Diponegoro, Sukorejo District, Blitar City, during the 2024/2025 academic year. By using puzzles, children are encouraged to focus on tasks requiring concentration and teamwork. The results show that puzzle games effectively reduce restless behaviors in hyperactive children, increase their ability to stay still and focus, and improve social skills such as sharing and collaborating. Additionally, these games help children manage their emotions, especially when facing challenges. Observations of interactions between teachers and children also indicate that this approach not only supports cognitive development but also enriches their social and emotional skills. Overall, the application of puzzle games has proven to be effective in managing hyperactive children in early childhood education, with active support from teachers and parents.